Assessment of convective heat transfer coefficient and mass of water evaporated from a single-slope passive solar still by different thermal models: an experimental validation. Issue 7 (3rd October 2017) - Sivakumar, V.; Ganapathy Sundaram, E.
Abstract: In this paper, an effort has been made to evaluate the convective heat transfer coefficient and mass of water evaporated from a single-slope passive solar still for different water depths (0.01, 0.015, 0.02 and 0.025 m) by various thermal models, namely Dunkle's model, Chen et al.'s model, Clark's model, Adhikari et al.'s model, Kumar and Tiwari's model, Zheng Hongfei et al.'s model and Tsilingiris's model. These models were studied and compared with our experimental work. Also, the energy and exergy efficiency were calculated and the percentage deviation between experimental and theoretical prediction is also listed out. The experimental validation of energy and exergy efficiency of single slope passive solar still using different thermal models was carried out at Chennai, Tamil Nadu, India. By comparing the theoretical values of the hourly yield with the experimental data it was found that Dunkle's, Chen et al.'s and Tsilingiris's models gave better conformity between the forecasted and experimental results. Kumar and Tiwari's model yield is very high, whereas Clark's model, Adhikari et al.'s model and Zheng Hongfei et al.'s model predict lower values as compared with our experimental results.